FINANCIAL SUSTAINABILITY OF ECONOMIC ENTITIES OF KAZAKHSTAN LIGHT INDUSTRY - G.T. Kunurkulzhayeva; А.А. Kurmanalina; G.K. Uashov; L.A. Kurmangaliyeva (Academic Journal of Physical and Chemical Sciences, 2019)
The article analyzes the development of light industry in the market of the Republic of Kazakhstan, by identifying regional features of the development of this industry and comparing their competitive characteristics. The novelty of the research lies in the adaptation of well-known theoretical tools to the peculiarities of the situation under study, as well as in the application of relatively new tools and methods for analyzing the development of light industry enterprises. The relevance of the study lies in the fact that given the significant role of light industry in ensuring economic and strategic security, employment of the working population and raising its standard of living in new geopolitical conditions, it is necessary to pay special attention to the development of this industry and provide it with substantial investment support, as is done by leading world countries. The study presents some indicators of light industry, characterizing its position in the Kazakhstan market, the level of development of the textile industry, as one of the developed light industry subsector, and directions for the further development of light industry. In the course of the study, techniques and methods of summary, grouping, ranking, coefficients, comparisons, and time series were used.